Young, British and searching: rethinking secularization through Gen Z - Sanders, Karen (Church, Communication and Culture, 2025)
‘Generation Z’ is a generational cohort more likely to choose ‘no religion’ as their preferred self-designation and to seek out their own personal approach to spirituality beyond institutional religion. This article analyses the findings of the British sample of a cross-national survey of 4,889 young people (18-29) from eight countries. It explores the religious identity and ethical views of British young people, including how their views align or diverge from doctrinal or cultural expectations of the three most prominent faith traditions in Britain: Catholicism, Anglicanism and Islam. The study reveals the complexity of young Britons’ navigation of faith and spirituality, and indicates that linear secularization narratives do not adequately reflect the reality of changing attitudes towards institutional religion. We argue that more nuanced interpretive frameworks that include the reality of human agency can better account for the diversity of belief and unbelief among Generation Z.